(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the pattern of cheiloscopic inheritance, transmitted from mother to daughter, and its applicability in human identification. Methodology: This was a cross-sectional study of a qualitative and quantitative nature, prepared in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE). The sample consisted of 30 dentistry students from the State University of Feira de Santana (UEFS), and their respective mothers. The method consisted of three steps: measurement of lip thickness, classification of the commissures of the lips and evaluation of the sulcular pattern, following the classification of Suzuki and Tsuchihashi. The data were analyzed statistically using Pearson’s chi-square and Fisher’s exact tests. Results: The most prevalent lip characteristics were the presence of mixed, thick / very thick lips and the lip commissure arranged horizontally. In the evaluation of the sulcular pattern, type I (complete vertical lines) and I ’(incomplete vertical lines) prevailed. The thickness and type of lip commissure showed greater potential for transmission from mother to daughters, when compared to the types of lip grooves. Conclusion: The analysis of the lips showed some characteristics that show greater similarity between mothers and daughters, with the pattern of the lip impressions being the characteristic of less similarity among the descendants studied.